Peran Modal Sosial Organisasi dalam Meningkatkan Kinerja Organisasi di PKP2A I Lembaga Administrasi Negara - Yenny Muliatty Hulu (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2018)
This research examines the issue of organizational social capital. This research tries to analyze the role of organizational social capital in improving the organizational performance, the efforts to develop the organizational social capital, and the constraints faced in optimizing the organizational social capital at PKP2A I LAN. This research employed a descriptive-explanative, qualitative method. The analysis results showed that the role of organizational social capital at PKP2A I LAN represented an important and fundamental factor in determining the organization's performance although the elements of social capital as a whole have not been optimally practiced by all employees in building cooperation to achieve the performance and objectives of the organization. In the context of PKP2A I LAN, it was found that the elements of social capital, such as mutual trust, mutual giving, mutual respect, participation, and commitment had relatively strong implications in achieving the organizational performance, compared to the values (IPIP) and norms. The efforts to develop the organizational social capital at PKP2A I LAN were conducted through formal and informal activities. The efforts through these activities provided positive implications for the socialization and internalization of various attitudes, values and norms that become important elements of organizational social capital at PKP2A I LAN